Validade concorrente e confiabilidade do aplicativo My jump 2 para medidas de potencia em jogadores de voleibol de praia - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Introduction: Beach volleyball is a sport derived from indoor volleyball and has physical demands such as the ability to sprint, change direction, vertical jumps and power in the lower and upper limbs. In this context, the search to adjust existing tests for the sandy surface has grown because it is understood that increasing specificity can help control the performance of these players. Objective: To investigate the concurrent validity and reliability of the My Jump 2 App to measure the height of different jumps in adult beach volleyball players. Materials and Methods: 26 male beach volleyball players (24.5±4.89 years old; 7.04±3.99 years of practice) completed all stages of the study. Participants were subjected to four different types of jumps on sandy ground, namely: i) Attack Countermovement; ii) Blocking countermovement; iii) Crouch Jump; iv) Countermovement, performed in a random session. Some of the participants were randomly selected to take the retest after 48 hours. Data collection was done through 2-D video using a cell phone (resolution of 1920x1080 pixels), with 4K footage, and a frequency of 60Hz. The images were subsequently evaluated using the KINOVEA system and the My Jump 2 App on the IOS platform. The data were processed using the intraclass correlation coefficient to verify the reliability of the measurements (test-retest) for the two measurement methods. Concurrent validity was analyzed using the Pearson correlation test followed by linear regression tests and the Bland-Altman graph to identify levels of agreement. Results: The coefficient of determination (r2) was 50% for the crouch jump, 54% for the counter movement jump, 59% for the CMJ in the blocking position and 65% for the CMJ in the attack position. As well, the Bland-Altman analysis showed agreement for the four types of jumps, with a bias of: CMJ Attack=-6.24cm; CMJ Lock=-5.37cm; SA=-5.08cm; CMJ=-6.91cm. The tests showed high intraclass correlation rates between days, both in the 2D two-dimensional kinematic analysis and in the My Jump 2 App, with values between 0.82 and 0.94. Conclusions: The My Jump 2 App showed a high bias, over estimating the values achieved by 2D kinematics, which inspires caution for a real understanding of the jump measurement, regardless of which jump is being evaluated. On the other hand, the reliability in the measurement between days ranged between good and excellent, indicating cohesion in the application of these measures to understand the response of the lower limb power measurement based on training processes for this variable for beach volleyball players.
Concurrent validity and reliability of the My jump 2 application for power measurements in beach volleyball players
Keywords: .; CIENCIAS DA SAUDE: EDUCACAO FISICA; Aptidão física; Desempenho atlético; Voleibol